2018
DOI: 10.3390/molecules23071540
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Comparative Evaluation of Novel Cationic Amphiphile C12-Man-Q as an Efficient DNA Delivery Agent In Vitro

Abstract: New amphiphilic 1,4-DHP derivative C12-Man-Q with remoted cationic moieties at positions 2 and 6 was synthesised to study DNA delivery activity. The results were compared with data obtained for cationic 1,4-DHP derivative D19, which is known to be the most efficient one among the previously tested 1,4-DHP amphiphiles. We analysed the effects of C12-Man-Q concentration, complexation media, and complex/cell contact time on the gene delivery effectiveness and cell viability. Transmission electron microscopy data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Previously, 3,5-bis(dodecyloxycarbonyl)-1,4-DHPs containing cationic moieties were elaborated as synthetic lipid-like compounds having promising gene delivery properties for DNA transfection; the basic structure-activity relationships have been verified for the cationic 1,4-DHP derivatives as gene delivery systems, and it has been shown that the molecular structure affected their self-assembling properties, pDNA-binding ability, and properties of the formed 1,4-DHP amphiphile-pDNA complexes [ 13 , 15 , 28 ]. The synthetic procedure for the amphiphilic compounds 1 – 7 , 9 – 22 , and 26 is displayed in Scheme 1 via a multistep sequence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, 3,5-bis(dodecyloxycarbonyl)-1,4-DHPs containing cationic moieties were elaborated as synthetic lipid-like compounds having promising gene delivery properties for DNA transfection; the basic structure-activity relationships have been verified for the cationic 1,4-DHP derivatives as gene delivery systems, and it has been shown that the molecular structure affected their self-assembling properties, pDNA-binding ability, and properties of the formed 1,4-DHP amphiphile-pDNA complexes [ 13 , 15 , 28 ]. The synthetic procedure for the amphiphilic compounds 1 – 7 , 9 – 22 , and 26 is displayed in Scheme 1 via a multistep sequence.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, for studies of targeted changes in the structure of corresponding dicationic compound 10 , which was found to be more active for DNA delivery among the tested 1,4-DHP amphiphiles [ 13 , 15 , 28 ], 1,1′,1 ″ ,1‴-((1,4-phenylenebis(3,5-bis((dodecyloxy)carbonyl)-1,4-dihydropyridine-4,2,6-triyl))tetrakis(methylene))tetrakis(pyridin-1-ium) tetrabromide ( 26 ) was synthesized as a double or a “dimeric” molecule of compound 10 and 1,1′-((3,5-bis(dodecyloxycarbonyl)-4-phenylpyridine-2,6-diyl)bis(methylene))-bis(pyridin-1-ium)dibromide ( 27 ) was prepared in accordance with what was reported in [ 14 ] as the oxidized form of compound 10 . For evaluation of the anion influence on cytotoxicity, 1,1′-((3,5-bis((dodecyloxy)carbonyl)-4-phenyl-1,4-dihydropyridine-2,6-diyl)bis(methylene))bis(pyridin-1-ium) ditetrafluoroborate ( 11 ) was synthesized from compound 10 after treating with NH 4 BF 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some representatives of this class show pDNA transfection activity; however, it is lower than for the corresponding 1,4-DHP amphiphiles [8]. Minor modifications, such as elongation by one methylene group of the distance between cationic moieties and the linker, also led to notable changes in the delivery activity of cationic 1,4-DHP [9]. It is possible to fill liposomes formed by amphiphilic 1,4-DHP derivatives with magnetic particles, which show targeted accumulation under the guidance of external magnetic fields [10].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, during the last decades, the development of new pyridinium moieties containing compounds based on a 1,4-DHP core has become an interesting area for medicinal chemistry research. Cationic 1,4-DHP amphiphiles having one or two cationic moieties and various length ester appendages, were found to be capable of transfecting pDNA into different cell lines in vitro [31,32], due to their self-assembling properties [33,34].…”
Section: Introductionmentioning
confidence: 99%